Genetic differentiation in functional traits among European sessile oak populations. (8th November 2019) - Torres-Ruiz, José M; Kremer, Antoine; Carins Murphy, Madeline R; Brodribb, Tim; Lamarque, Laurent J; Truffaut, Laura; Bonne, Fabrice; Ducousso, Alexis; Delzon, Sylvain
Abstract: The vulnerability of forest species and tree populations to climate change is related to the exposure of the ecosystem to extreme climatic conditions and to the adaptive capacity of the population to cope with those conditions. Adaptive capacity is a relatively under-researched topic within the forest science community, and there is an urgent need to understand to what extent particular combinations of traits have been shaped by natural selection under climatic gradients, potentially resulting in adaptive multi-trait associations. Thus, our aim was to quantify genetic variation in several leaf and woody traits that may contribute to multi-trait associations in which intra-specific variation could represent a source for species adaptation to climate change. A multi-trait approach was performed using nine Quercus petraea provenances originating from different locations that cover most of the species' distribution range over Europe and that were grown in a common garden. Multiple adaptive differences were observed between oak provenances but also some evolutionary stasis. In addition, our results revealed higher genetic differentiation in traits related to phenology and growth than in those related to xylem anatomy, physiology and hydraulics, for which no genetic differentiation was observed. The multiple associations between those traits and climate variables resulting from multivariate and path analyses suggest a multi-trait association largely involving phenological and growth traits for Q. petraea .